Process intensification and integration of solar heat generation in the Chinese condiment sector – A case study of a medium sized Beijing based factory. (December 2015) - Sturm, Barbara; Meyers, Steven; Zhang, Yongjie; Law, Richard; Siqueiros Valencia, Eric J.; Bao, Huashan; Wang, Yaodong; Chen, Haisheng
Highlights: Solar energy was investigated as a renewable source of process heat. Photovoltaic and/or solar thermal were considered for process heat generation. Flat plate collectors were the most economical solution for hot water generation. Steam generation was most economical with a cascade of photovoltaic and flat plate collectors. Implementing both technologies leads to a reduction in utility import of 14%. Abstract: Over the last decade, energy prices in China have risen dramatically. At the same time, extensive use of coal fired energy provision systems in industry has led to serious environmental and economic problems translating to an economic damage of an estimated 10% of the Gross Domestic Product. This has led to increasing awareness in the process industries of the need to save energy whilst replacing conventional energy sources with renewable ones. An energy audit was conducted for a soy sauce production facility in Beijing, which aimed to reduce its thermal energy demand through process intensification and to integrate renewable energy. Their current supply of thermal energy came directly from a district steam network, which was both directly consumed and downgraded via heat exchangers. It was determined that the best two solar integration locations would be in the pre-heating/mixing of raw ingredients to 60 °C and the subsequent direct steaming of the mixture to 120 °C. Three different systems for supplementing steam were investigated: (1) a traditional solar thermal heating system; (2) a system consisting of mono crystalline photovoltaic panels coupled with either a resistance heater or electric steam generator; and (3) a cascading system consisting of two types of solar thermal collectors, photovoltaic panels, and an electric steam generator. Comparisons of systems 1 and 2 were made for the heating of mixing water, and systems 1, 2, and 3 for saturated steam generation. Results showed that for the heating of process water, flat plate solar collectors performed best with an estimated 20 year Levelised Cost of Energy of 0.063 €/kW h. Steam generation was most cost effective with a cascade system of photovoltaic and flat plate collectors, with an estimated 20 year Levelised Cost of Energy of 0.145 €/kW h. The model predicts that integration of this technology would lead to a reduction of 14% in heating utility demand.